1997
DOI: 10.1038/39282
|View full text |Cite
|
Sign up to set email alerts
|

Bending and buckling of carbon nanotubes under large strain

Abstract: The curling of a graphitic sheet to form carbon nanotubes produces a class of materials that seem to have extraordinary electrical and mechanical properties. In particular, the high elastic modulus of the graphite sheets means that the nanotubes might be stiffer and stronger than any other known material, with beneficial consequences for their application in composite bulk materials and as individual elements of nanometre-scale devices and sensors. The mechanical properties are predicted to be sensitive to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
744
2
8

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,416 publications
(800 citation statements)
references
References 18 publications
19
744
2
8
Order By: Relevance
“…The values for the Young's modulus were found to be between 0.32 and 1.47 TPa [61][62][63][64][65][66][67][68][69][70]. Falvo et al [61] observed that MWNTs could be bent at sharp angles without undergoing any structural fracturing using an AFM tip. Endo et al [62] observed that while breaking vapor-grown CNTs in liquid nitrogen, an inner tubule could survive this pressure.…”
Section: Mechanical Properties Of Cntsmentioning
confidence: 99%
“…The values for the Young's modulus were found to be between 0.32 and 1.47 TPa [61][62][63][64][65][66][67][68][69][70]. Falvo et al [61] observed that MWNTs could be bent at sharp angles without undergoing any structural fracturing using an AFM tip. Endo et al [62] observed that while breaking vapor-grown CNTs in liquid nitrogen, an inner tubule could survive this pressure.…”
Section: Mechanical Properties Of Cntsmentioning
confidence: 99%
“…C zH corresponds to the C-C bond length coefficient terminated with H. Subscripts B corresponds to bulk. From the measured melting point [65,66] of carbon nanotubes, elastic modulus [63,64], and the C1s electron binding energy shift [67], we have obtained m = 2.56.…”
Section: Bols-hm Parameter For Graphenementioning
confidence: 99%
“…For example, based on the Young's modulus [63,64], the melting temperature [65,66] of carbon nanotube and the energy shift of C1s level of grapheme [67], we obtained the bond nature parameter m = 2.56 of carbon. Figure 3 compares the relation between hopping integrals and the C-C bond length derived by BOLS-HM and obtained by TB fitting from DFT results [33].…”
Section: Enhancement Of Onsite and Hopping Integralsmentioning
confidence: 99%
“…Tremendous efforts have been made to solve the challenges. Techniques, such as scanning-probe-microscopeassisted patterning, [75][76][77] chemical vapor deposition, [78][79][80] template-directed assembly, [81][82][83] and dielectrophoresis deposition, [84][85][86][87] have been developed trying to achieve controlled integration of CNTs. However, existing drawbacks (such as high processing temperature, slow processing speed, coarse control, liquid phase processing/contamination, low reliability, low yield, and high cost) of individual approaches [75][76][77][78][79][80][81][82][83][84][85][86][87] make it difficult to develop a high- performance-on-demand approach for fabricating CNTbased devices.…”
Section: Controlled Growth and Integration Of One-dimensional Camentioning
confidence: 99%